2014
DOI: 10.1111/bjh.12978
|View full text |Cite
|
Sign up to set email alerts
|

SL‐401 and SL‐501, targeted therapeutics directed at the interleukin‐3 receptor, inhibit the growth of leukaemic cells and stem cells in advanced phase chronic myeloid leukaemia

Abstract: SUMMARY While imatinib and other tyrosine kinase inhibitors (TKIs) are highly efficacious in the treatment of chronic myeloid leukaemia (CML), some patients become refractory to these therapies. After confirming that interleukin-3 receptor (IL3R, CD123) is highly expressed on CD34+/CD38− BCR-ABL1+ CML stem cells, we investigated whether targeting IL3R with diphtheria toxin (DT)-IL3 fusion proteins SL-401 (DT388-IL3) and SL-501 (DT388-IL3[K116W]) could eradicate these stem cells. SL-401 and SL-501 inhibited cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 48 publications
(67 reference statements)
1
30
0
1
Order By: Relevance
“…A recent study also demonstrated anti-CSC activity of SL-401 in advanced CML. 40 Together, our data suggests that SL-401 may target tumor-initiating stem-like cells and thereby abrogate development of drug-resistance in MM.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study also demonstrated anti-CSC activity of SL-401 in advanced CML. 40 Together, our data suggests that SL-401 may target tumor-initiating stem-like cells and thereby abrogate development of drug-resistance in MM.…”
Section: Discussionmentioning
confidence: 66%
“…132,133 Because activation of the Hedgehog signaling pathway could contribute to the development of leukemic stem cells, CMML patients can be included in a phase 1 study of a smoothened antagonist. 134 Finally, high expression of interleukin-3 receptor (CD123) in leukemic stem cells led exploration of the efficacy of SL-401, a diphtheria toxininterleukin-3 fusion protein, 135 in patients with hematological malignancies including CMML. Another characteristic feature of CMML is the frequent mutations of a splicing gene.…”
Section: Currently Explored Therapeutic Strategies In Cmml Patientsmentioning
confidence: 99%
“…55 Increased expression of CD123/IL3Ra has subsequently been demonstrated in related malignancies, including MDS, chronic myeloid leukemia, and aggressive NHLs, among others. [56][57][58] The a subunit of IL-3R is a type I transmembrane glycoprotein (cytokine receptor superfamily) that co-dimers with CD131 (common b chain). Leukemic blasts seem to differentially express IL-3Ra compared with normal stem cells, 55 and this may relate to differential sensitivity to therapy.…”
Section: Novel Therapymentioning
confidence: 99%